Hydraulic properties of rice and the response of gas exchange to water stress - Stiller, Volker; Lafitte, H. Renee; Sperry, John S. (Oxford University Press, 2003)
We investigated the role of xylem cavitation, plant hydraulic conductance, and root pressure in the response of rice (Oryza sativa) gas exchange to water stress. In the field (Philippines), the percentage loss of xylem conductivity (PLC) from cavitation exceeded 60% in leaves even in watered controls. The PLC versus leaf water potential relationship indicated diurnal refilling of cavitated xylem. The leaf water potential causing 50 PLC (P50) was –1.6 MPa and did not differ between upland versus lowland rice varieties. Greenhouse-grown varieties (Utah) were more resistant to cavitation with a 50 PLC of –1.9 MPa but also showed no difference between varieties. Six-day droughts caused concomitant reductions in leaf-specific photosynthetic rate, leaf diffusive conductance, and soil-leaf hydraulic conductance that were associated with cavitation-inducing water potentials and the disappearance of nightly root pressure. The return of root pressure after drought was associated with the complete recovery of leaf diffusive conductance, leaf-specific photosynthetic rate, and soil-leaf hydraulic conductance. Root pressure after the 6-d drought (61.2 ± 8.8 kPa) was stimulated 7-fold compared with well-watered plants before drought (8.5 ± 3.8 kPa). The results indicate: (a) that xylem cavitation plays a major role in the reduction of plant hydraulic conductance during drought, and (b) that rice can readily reverse cavitation, possibly aided by nocturnal root pressure.